Fourth Wave Feminism in Indonesia: Body Shaming Through Social Media Phenomenon - Noviyanti Soleman; Rifki Elindawati (Universitas Muhammadiyah Yogyakarta, 2019)
Recently, Indonesia has been horrified by the phenomenon of body shaming through social media. Even though this has happened previously, but now the victims take serious action to respond the situation, including filed reports on the police based on violations of the ITE Law Article 27 paragraph (3) in conjunction with Article 45 paragraph (3) of Law No 11 of 2008. However, some people still do the body shaming especially through social media by disguising body size, imperfection and appearance. Based on the data, there are 966 cases of body shaming in 2018. Furthermore, this research aims to assess the body shaming through social media phenomenon in Indonesia which has the relations with the fourth wave feminism issues. To answer the research question, the writers use objectification theory and feminist constructivism approach. This study deployed the qualitative research instrument by primary and secondary data.